PENERAPAN METODE DEMONSTRASI UNTUK MENINGKATKAN HASIL BELAJAR IPA MATERI KERANGKA TUBUH MANUSIA PADA SISWA KELAS 4 SDN 2 PESISIR SEMESTER I TAHUN PELAJARAN 2012/2013 - Misbahul Munir; Putu Eka Suarmika (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2013)
The condition of learning in SDN 2 Coast does not meet expectations. Percentage of mastery learning students in grades 4 obtained from the daily tests on the skeletal material nanusia showed that students who completed the study only about 45%. The purpose of this study were: 1) To clarify the application demonstration method to improve the learning outcomes of the human skeleton material science in grade 4 Coastal SDN 2; 2) To improve student learning outcomes in the material science of the human skeleton with the application of methods of demonstration. The subjects were students of class 4 subdistricts Coastal Besuki SDN 2 Situbondo the odd semester of the school year 2012/2013, totaling 22 students consisting of 7 male students and 15 female students. The research method in this study is action research and the study design used a model of Kemmis and Taggart. Student learning outcomes using the demonstration has increased significantly from the first cycle to the second cycle. In the first cycle of learning outcomes of students who have mastery learning as many as 15 students. While students who have not achieved mastery learning as much as 7 students. In the second cycle learning outcomes of students who have mastery learning as much as 19 students. While students who have not achieved mastery learning as much as 3 students